2019
DOI: 10.1002/ecs2.2655
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation and precipitation shifts interact to alter organic and inorganic carbon storage in cold desert soils

Abstract: Dryland ecosystems are experiencing shifts in rainfall and plant community composition, which are expected to alter cycling and storage of soil carbon (C). Few experiments have been conducted to examine long‐term effects on (1) soil organic C (SOC) pools throughout the soil profile, and (2) soil inorganic C (SIC) pools as they relate to dynamic changes in C storage and climate change. We measured SOC and SIC from 0 to 1 m beneath plants and in adjacent interplant microsites following nearly 20 yr of experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Along the natural salinity gradient, the SIC was higher at low salinity, < 6suggesting that salinity stress influences SIC cycling (Wang et al, 2019). SIC has two potential determinants: (1) uptake and deposition of atmospheric CO 2 by base cation (Xie et al, 2009;Raheb et al, 2017), and (2) re-distribution of respired CO 2 among microorganisms and roots (Huber et al, 2019). pH markedly influences the magnitude of SIC, soil acidity at low pH results in SIC loss, and soil alkalinity at high pH increases atmospheric and soil CO 2 absorption of base cations (Liu et al, 2020a;Raza et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Along the natural salinity gradient, the SIC was higher at low salinity, < 6suggesting that salinity stress influences SIC cycling (Wang et al, 2019). SIC has two potential determinants: (1) uptake and deposition of atmospheric CO 2 by base cation (Xie et al, 2009;Raheb et al, 2017), and (2) re-distribution of respired CO 2 among microorganisms and roots (Huber et al, 2019). pH markedly influences the magnitude of SIC, soil acidity at low pH results in SIC loss, and soil alkalinity at high pH increases atmospheric and soil CO 2 absorption of base cations (Liu et al, 2020a;Raza et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Huber et al (2019) also found that increases in winter rainfall can turn soil under sagebrush plants into a net C source. In stages III and IV, litter C:N ratio was not a significant part of the model, perhaps because the litter layer was composed mainly B. tectorum detritus, and the C:N ratio did not differ between years.…”
mentioning
confidence: 90%
“…In semiarid shrubland systems of the western United States, invasion by herbaceous species can interact with drought to reduce an ecosystem's capacity to sequester C (Esch et al, 2019). A. tridentata communities are a C sink during the growing season and this is amplified with increased summer precipitation (Germino et al, 2015;Huber et al, 2019). However, they may become a source with increases in dormant season precipitation (Huber et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant-assimilated inorganic C (i.e., CO 2 ) is the major SOC source that atmospheric and soil-released CO 2 fixed via photosynthesis contributes to the SOC pool through litter and root inputs (Fig. 1; Le Quéré et al, 2018;Huber et al, 2019). Few studies have reported that microorganisms can also utilize inorganic C to maintain cell proliferation and growth (Zamanian et al, 2016;, whether microorganisms convert SIC to SOC remains unclear owing to the lack of a microbial indicator between SIC…”
Section: Introductionmentioning
confidence: 99%